2018
DOI: 10.3390/su10103692
|View full text |Cite
|
Sign up to set email alerts
|

Markov-Chain Simulation-Based Analysis of Human Resource Structure: How Staff Deployment and Staffing Affect Sustainable Human Resource Strategy

Abstract: Manufacturing and service processes are composed of several elements: Technical, financial, logistics, information and human resources. Staff deployment and staffing is an essential problem in the human resource management domain because the structure of employees would be continuously in an optimal relationship to the jobs to be performed. This paper proposes a conceptual model for the analysis of human resource deployment processes. After a systematic literature review, it was found that algorithms are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 69 publications
1
20
0
2
Order By: Relevance
“…As noted by Bányai et al [16], the human factor cannot be neglected in manufacturing. Thus, we can presume that the manufacturing flexibility, the measure of operational performance, will vary depending on how firms leverage the human resources.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Bányai et al [16], the human factor cannot be neglected in manufacturing. Thus, we can presume that the manufacturing flexibility, the measure of operational performance, will vary depending on how firms leverage the human resources.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining and retaining high-quality employees is, thus, a survival strategy for hospitality practitioners to reach a long-term successful business from the perspective of sustainability [24]. Several studies have integrated sustainable HRM into the workplace [28,29], yet few have examined sustainable HRM under a research framework, especially in the hospitality industry, to better comprehend its effects on human work performance.…”
Section: Sustainable Hrmmentioning
confidence: 99%
“…Line production supervisors and operators play a key role n the implementation of the JIT philosophy. Researchers such as García, Rivera, Blanco, Jiménez and Martínez [18] found that both training and skills development increased operator empowerment during the JIT implementation process, and Bányai, et al [39] indicated the importance of human resource strategy for JIS, maintaining material flow along the SC; however, the allocation of resources necessary to these training programs depends on managers [40]. In this sense, senior managers must prioritize training projects focused on employee multifunctionality as an strategy [41].…”
Section: Human Resources Integration (Hri)mentioning
confidence: 99%
“…However, as experts point out, companies should also promote job rotation to increase motivation among employees and offer them new challenges, where they can develop new skills and support waste reducing, but also, for increase the JIS and reducing buffers between work stations [24,39]. Likewise, as Esmaeilian, et al [43] claim, managers must encourage teamwork during the JIT implementation process, especially during decision-making and problem-solving processes, to preserve support material flow in a JIS.…”
Section: Human Resources Integration (Hri)mentioning
confidence: 99%